Phantoms on the bookshelves - Bonnet, Jacques, 1949-; Reynolds, Sian. (New York : Overlook Press, 2012)
This study on the art of living with books considers how our personal libraries reveal our true nature, offering up delicious anecdotes along the way.
Bibliografija: str. 125-133.
Keywords: privatne knjižnice; bibliomanija; kolekcionarstvo - knjige; knjige i čitanje